Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
see explanation
Step-by-step explanation:
Given the 2 equations
x + y = 1 → (1)
ax - by = c → (2)
In (1) subtract y from both sides
x = 1 - y → (3)
Substitute x = 1 - y into (2)
a(1 - y) - by = c ← distribute left side
a - ay - by = c ( subtract a from both sides )
- ay - by = c - a ( multiply through by - 1 )
ay + by = a - c ← factor out y from each term on the left side
y(a + b) = a - c ← divide both sides by (a + b)
y = [tex]\frac{a-c}{a+b}[/tex] ← substitute into (3)
x = 1 - [tex]\frac{a-c}{a+b}[/tex] = [tex]\frac{a+b}{a+b}[/tex] - [tex]\frac{a-c}{a+b}[/tex] = [tex]\frac{a+b-a+c}{a+b}[/tex] = [tex]\frac{b+c}{a+b}[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.